A Review on Geopolymer Technology for Lunar Base Construction - Lee, S.; Van Riessen, Arie (MDPI, 2022)
Geopolymer is a synthetic amorphous aluminosilicate material that can be used as an inorganic binder to replace ordinary Portland cement. Geopolymer is produced by mixing aluminosilicate source materials with alkali activators and curing the mixture either at ambient or low temperatures. Geopolymer research for lunar-based construction is actively underway to enable astronauts to stay on the moon for long periods. This research has been spurred on by earnest discussions of in situ resource utilization (ISRU). Recent research shows that the lunar regolith simulant-based geopolymers have high application potential to protect astronauts from the harsh moon environment. However, not all the simulants perfectly reproduce the lunar regolith, and the characteristics of the lunar regolith vary depending on the site. Issues remain regarding the applicability of geopolymer technology to contribute to ISRU through an elaborate and systematic plan of experiments. In this paper, the potential of geopolymers is assessed as a lunar-based construction material with the latest research results. Future work to develop the lunar regolith-based geopolymer technology is also proposed.